Re-imagining Language and Literature for the 21st Century. - Duangsamosorn, Suthira (Textxet. Studies in Comparative Literature, 49., 2005)
In 28 essays selected from the proceedings of the XXII International Congress of FILLM held at Assumption University, Bangkok, scholars and teachers of languages and literatures have noted, bemoaned and analyzed the waning influence of the humanities to varying degrees. They have raised questions, offered solutions and vigorously defended their languages and literatures, often in no uncertain terms - not as a politically correct thing to do, but as a human obligation. The papers presented here are true to the spirit of the Congress from the moment of the keynote address to what followed in a sp.